Least cost diet for children two to three years in Malaysia using linear programming approach / Nor Hayati Binti Shafii, Rohana Alias and Noradilla Radzuan - Shafii, Nor Hayati; Alias, Rohana; Radzuan, Noradilla (UiTM Cawangan Perlis, 2018)
The early period of life, namely from birth to two years of age is critical for the promotion o f optimal growth, brain development as well as health and behavioural development. Thus, attaining the daily required nutrition during this stage of life is very crucial since nutrition is strongly associated with a child's development at a very young age . It is a major challenge for Malaysians to ensure children get a balanced diet, especially children from families of low socioeconomic status. As reported in the Edge Weekly, the review found that 24.9% or nearly one in four children in Malaysia experien ced moderate or severe food insecurity due to financial constraints. In this study, a linear programming diet model is used to determine an affordable cheapest food basket that satisfies the daily recommended nutritional requirements for children between two to three years old in Malaysia. POM -QM for Windows Version 5.2 by Howard J. Weiss is used. Initial finding shows that the average costs are RM2.69. This food basket consists of 474g of eggs, 55g of tofu, 29g of papaya, 5g of spinach and 201g of potato. With this food basket and estimated food expenditure, parents can save for 40% of their child's daily food expenditure.